Malignant peripheral nerve sheath tumor with lymph node metastasis: an uncommon presentation - Shreshtha, Suruchi (International Surgery Journal, 2017)
MPNST is a rare soft tissue neoplasm that accounts for less than 10 % of all soft tissue sarcomas. These tumors often affect males between 20 to 50 years, often with NF1, These with predilection for buttocks, thigh, brachial plexus, upper arm and paraspinal region. MPNST spread perineurally or hematogenously to lungs. Lymph node metastasis is seen in less than 5% cases of all sarcomas. This is a case of 46 year old male with NF-1 with MPNST posterior abdominal wall. The patient had metastatic pleural effusion in the absence of lung metastasis, along with widespread axillary, retroperitoneal and inguinal lymph node metastasis. Thus, although lymph node metastasis from MPNST is rare, this case expands our knowledge of the clinical behavior of MPNST.